Responses of an African tall-grass (Hyparrhenia filipendula stapf.) to defoliation and limitations of water and nitrogen - Coughenour, M B; McNaughton, S J; Wallace, L L (Oecologia, 1985)
Hyparrhenia filipendula stapf., a tall (1-1.5 m) perennial grass common in dry-subhumid African savannas, was collected from Serengeti National Park in Tanzania, propagated vegetatively, and grown in controlled environments simulating conditions in nature. Plants were subjected to a factorial experiment with combinations of watering frequency, nitrogen supply, clipping height (10 and 15 cm) and clipping frequency (7 and 14 d). Biomass yield and allocation to various tissue types, morphometric traits, and growth processes were measured.Watering frequency affected leaf elongation rate while nitrogen affected tiller number. Clipped yield was strongly correlated with leaf elongation rate but not tiller number, therefore it was primarily controlled by the activities of intercalary rather than apical meristems. There was a negative exponential relationship between tillering and clipped yield per tiller. Plants that received both high nitrogen and high water closely followed a-3/2 power law in this tradeoff. The fraction of total net photosynthate allocated to roots was not significantly related to any environmental treatment. Root and crown growths were not affected by defoliation treatment; leaf blade and stem growths were inhibited; and sheaths were inhibited only under low water.Despite a tall stature, H. filipendula tolerated herbivory by increased photosynthetic rate (Wallace et al. 1984), through continued production of young tissues by intercalary meristems balanced against tiller number, and by a statistically constant proportional allocation to roots. Clipped yield increased only when both nitrogen and water were abundant, and then, proportional clipped yield did not surpass an upper asymptotic limit.